TEACHING SPEAKING USING PICTURE STRIP STORY TO THE TENTH GRADE STUDENTS OF MA SEJAHTERA PARE IN THE ACADEMIC YEAR OF 2019/2020 - Wahyuni, Sri (Jurnal Simki Pedagogia, 2019)
Speaking ability is an interactive process of constructing meaning that involves producing and receiving and processing information. While, speaking ability is expressing ideas, opinions, or feeling to other by using words or sounds articulation in order to inform, to persuade and to entertain. In speaking learning the students get problems. Some of students sometimes cannot communicate well in English language and they get difficulties in speaking test. The problem comes from the element of speaking, accuracy, fluency, coherency, pronoun, and spelling. Therefore, the teacher should have a good method to make the students will not fell bored and improve their speaking ability. In this research, the researcher used Picture strip story. Picture strip story also can help a teacher more effective to teach their students such as delivering the material. The material in this research was recount text. Recount text is one of the example of story genres in recount text, it reconstructs past experience. It means that recount text tells about something that has happened. Its function is to entertain or amuse the readers. This research, the used true experimental design. And quantitative approach to know the student’s speaking ability. The data obtained were analysed using statistical formula. In this case, the researcher used t-test. The population of this research was the tenth grade students of MA Sejahtera Pare, of purposive which students consisted of 25 students with equal speaking ability. The research was carried out from June 2019 up to January 2020. After collecting the data, the next step was analyzing them by using SPSS vs 23.0 especially using paired sample t-test to know is there any significant effect of picture strip story to the students’ speaking ability. The result showed that the students’ speaking ability increased after being taught using picture strip story. It was proven by the mean after being taught using picture strip story (0.11707) was higher than that before being taught using picture strip story (11.707). The result report that the t-test was higher than the table sample ( 11.707 > 0.11707) it means that Ho was rejected and Ha was accepted. In the conclusion, picture strip story is an effective media used in teaching speaking. It can help the students to speak up without being afraid of making mistakes.